Protected area network insufficiently represents climatic niches of endemic plants in a Global Biodiversity Hotspot. (November 2022) - Ludovicy, Simon; Noroozi, Jalil; Semenchuk, Philipp; Moser, Dietmar; Wessely, Johannes; Talebi, Amir; Dullinger, Stefan
Abstract: Protected Areas (PA) play a pivotal role in conservation biology. Climate change challenges the concept of static PAs as species may not find suitable climatic conditions in the PAs designed to protect them in the future. Here, we assess this emerging mismatch for the endemic mountain flora of the Iranian Plateau, the main part of the Irano-Anatolian global biodiversity hotspot. We compare the climatic requirements of each of 1277 endemic plant species with the climatic conditions offered by those parts of the Iranian PA network that are within the dispersal range of each species. We undertake this comparison for current climatic conditions and the conditions predicted for the years 2050 and 2070 under the climatic scenarios RCP4.5 und RCP8.5. We find that 50 % of the species climatic niche space is represented in the PA network under current conditions. Depending on the climatic scenario and time frame, representation will decrease to 15–25 % in the future. Species of lowest and highest elevations, and, in particular, species with narrow ranges, are predicted to face the most pronounced losses of climatic representation in PAs. We conclude that the contribution of the current Iranian PA network to protecting the rich endemic flora of the country under climate change is limited. The network overrepresents climatically homogenous desert ecosystems and neglects endemism hotspots of high mountain chains. Efficient conservation planning in this biodiversity hotspot should focus on expanding elevational gradients within PAs and prioritize the protection of narrow range, low and high elevation species.